Imaging of Total Ankle Arthroplasty: Normal Imaging Findings and Hardware Complications - Omar, Imran M.; Abboud, Samir F.; Youngner, Jonathan M. (Seminars in Musculoskeletal Radiology, 2019)
End-stage ankle osteoarthritis often significantly impacts patients' quality of life. This can be managed surgically either by ankle arthrodesis or total ankle arthroplasty (TAA). Although ankle arthrodesis is considered by some as the standard-of-care surgical option for this condition, it restricts range of motion and may lead to accelerated osteoarthritis of neighboring joints. Better understanding of ankle biomechanics, the biological effects of orthopaedic devices, and new surgical techniques have led to significant improvements in the designs of TAAs, and over the last several decades TAA has been used increasingly to treat patients with end-stage tibiotalar osteoarthritis. However, complication and ultimate failure rates remain greater than those seen with total knee and hip arthroplasty, and imaging is often critical in determining whether a prosthesis is beginning to fail. As a result, imagers should be familiar with the basic types of TAAs in clinical use, the normal radiographic appearances, as well as the common complications seen with this procedure.
Keywords: ankle; tibiotalar; arthroplasty; imaging; complications